COPING STRATEGIES OF STUDENT-ATHLETES WITH DIFFERENT LEVEL OF EMOTIONAL BURNOUT - Tatyanina, L.G.; Vakhnin, N.A.; Sazonova, N.N.; Sorokin, S.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the relationship between coping strategies and the level of emotional burnout among student-athletes. Methods and structure of the study. The following research methods were used: the questionnaire "Emotional burnout" (author V.V. Boyko); method "Coping behavior in stressful situations" (authors S. Norman, D. Endler, D. James, M. Parker, adapted by T.A. Kryukova), method for determining the psychophysical potential of the body (authors G.V. Rudenko, Yu .A. Dubrovskaya, I.V. Bobrov). The study involved 92 2nd-4th year students of St. Petersburg universities aged 19 to 22 who actively participate in sports competitions in swimming and cross-country skiing. Results and conclusions. A high risk of developing a symptom complex of emotional burnout in student-athletes was determined. Relationships between the used coping strategies and the level of emotional burnout of students are revealed. The results of the study indicate that the mechanisms of coping strategies and stress resistance of an individual are interrelated and affect the adaptive potential of an individual. The use of problem-oriented coping strategies as a mechanism for coping with stressful situations is more effective than the use of “emotionally oriented”, “distraction” and “avoidance” coping strategies, which give the individual temporary relief, but are not aimed at eliminating the stressful situation.